Risk Factors for Infection, Predictors of Severe Disease, and Antibody Response to COVID-19 in Patients With Inflammatory Rheumatic Diseases in Portugal—A Multicenter, Nationwide Study - Cruz-Machado, Ana Rita; Barreira, Sofia C.; Bandeira, Matilde; Veldhoen, Marc; Gomes, Andreia; Serrano, Marta; Duarte, Catarina; Rato, Maria; Miguel Fernandes, Bruno; Garcia, Salomé; Pinheiro, Filipe; Bernardes, Miguel; et al. (Frontiers in Medicine, 2022)
Objective: To identify risk factors for SARS-CoV-2 infection and for severe/critical COVID-19, and to assess the humoral response after COVID-19 in these patients. Methods: nationwide study of adult patients with inflammatory RMDs prospectively followed in the Rheumatic Diseases Portuguese Register – Reuma.pt – during the first 6 months of the pandemic. We compared patients with COVID-19 with those who did not develop the disease and patients with mild/moderate disease with those exhibiting severe/critical COVID-19. IgG antibodies against SARS-CoV-2 were measured ≥ 3 months after infection and results were compared with matched controls. Results: 162 cases of COVID-19 were registered in a total of 6363 appointments. Patients treated with TNF inhibitors (TNFi) (OR=0.160, 95%CI 0.099-0.260, p<0.001) and tocilizumab (OR 0.147, 95%CI 0.053-0.408, p<0.001) had reduced odds of infection. Further, TNFi tended to be protective of severe and critical disease. Older age, major comorbidities, and rituximab were associated with an increased risk of infection and worse prognosis. Most patients with inflammatory RMDs (86.2%) developed a robust antibody response. Seroconversion was associated with symptomatic disease (OR 13.46, 95%CI 2.21-81.85, p=0.005) and tended to be blunted by TNFi (OR 0.17, 95%CI 0.03-1.05; p=0.057). Conclusions: TNFi and tocilizumab reduced the risk of infection by SARS-CoV-2. Treatment with TNFi also tended to reduce rates of severe disease and seroconversion. Older age, general comorbidities and rituximab were associated with increased risk for infection and worse prognosis, in line with previous reports. Most patients with RMDs developed a proper antibody response after COVID-19, particularly if they had symptomatic disease.